Gene delivery system of pDNA using the blood glycoprotein fetuin. (9th August 2018) - Kodama, Yukinobu; Hanamura, Hiroki; Muro, Takahiro; Nakagawa, Hiroo; Kurosaki, Tomoaki; Nakamura, Tadahiro; Kitahara, Takashi; Kawakami, Shigeru; Nakashima, Mikiro; Sasaki, Hitoshi
Abstract: Fetuin is a biocompatible plasma protein and strongly enhances phagocytosis of bacteria, DNA and apoptotic cells by peripheral blood cells such as monocytes, macrophages and dendritic cells. We developed a novel gene delivery system: ternary complexes constructed with pDNA, polyethylenimine (PEI) and fetuin. Without covalent binding, fetuin was able to coat pDNA–PEI complexes, and stable anionic nanoparticles formed at a weight ratio greater than 30. Optimised pDNA–PEI–fetuin complexes significantly decreased the cytotoxicity of pDNA–PEI complexes in the melanoma cell line B16F10. Furthermore, the pDNA–PEI–fetuin complexes had higher transgene efficiency compared to that of commercial lipofectin previously reported in B16F10 cells despite an anionic surface. The pDNA–PEI–fetuin complexes did not agglutinate with erythrocytes. The pDNA–PEI–fetuin complexes had high gene expression in the spleen after intravenous administration in mice. Thus, the pDNA–PEI–fetuin complexes were a useful in vivo gene delivery system with tropism for the spleen.